2009
DOI: 10.1161/circresaha.109.199547
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Oxidative Modification

Abstract: Abstract-Angiotensin II (Ang II) inhibits the cardiac sarcolemmal Na ϩ -K ϩ pump via protein kinase (PK)C-dependent activation of NADPH oxidase. We examined whether this is mediated by oxidative modification of the pump subunits. We detected glutathionylation of ␤ 1 , but not ␣ 1 , subunits in rabbit ventricular myocytes at baseline. ␤ 1 Subunit glutathionylation was increased by peroxynitrite (ONOO Ϫ ), paraquat, or activation of NADPH oxidase by Ang II. Increased glutathionylation was associated with decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 24 publications
9
108
0
Order By: Relevance
“…This increase in pump current was abolished by L‐ N G ‐nitroarginine methyl ester, showing that stimulation was mediated by eNOS‐derived NO production enhanced by ex vivo supplementation of BH 4 . In previous reports we have shown that NO generation from eNOS stimulates the Na + ‐K + pump,10, 38 and conditions that cause eNOS uncoupling inhibit the Na + ‐K + pump 24, 3940 where changes in redox milieu are sensed by eNOS and transduced to regulation of the Na + ‐K + pump function via redox‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This increase in pump current was abolished by L‐ N G ‐nitroarginine methyl ester, showing that stimulation was mediated by eNOS‐derived NO production enhanced by ex vivo supplementation of BH 4 . In previous reports we have shown that NO generation from eNOS stimulates the Na + ‐K + pump,10, 38 and conditions that cause eNOS uncoupling inhibit the Na + ‐K + pump 24, 3940 where changes in redox milieu are sensed by eNOS and transduced to regulation of the Na + ‐K + pump function via redox‐dependent mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…We tested this by examining glutathionylation of the highly abundant, ubiquitous membrane protein Na + ‐K + pump, which mediates inhibition of the pump function in cardiac myocytes24 and vascular smooth muscle cells 23. Alloxan, at high concentrations in vitro (1 mmol/L, 37°C, 30 minutes), reflecting the pancreatotoxic diabetogenic doses used in vivo, increased glutathionylation of the β 1 Na + ‐K + pump subunit (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathionylation inhibits the pump by stabilizing its E1 conformation. Figtree et al [27] showed that glutathionylation of NKA is reversible in nature where glutaredoxin1 (GRX1) facilitated deglutathionylation of the pump. In BPASMCs, we determined the presence of GRX1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of peroxynitrite (ONOO -) or Snitrosoglutathione (GSNO, 10-500 lM) to induce S-glutathionylation is also found in the literature (12,38,125,129). The application of peroxynitrite is of high physiological relevance but as peroxynitrite can also induce other modification including S-nitrosylation, additional experiments should be performed to further dissect the exact modification mechanism.…”
Section: Induction Of S-glutathionylationmentioning
confidence: 99%